Glomerular filtration rate evaluation and its comparison with international standard values in a large populationbased study - Seyed Javad Hoseini; Ehsan Mosa Farkhani; Hamid Reza Bahrami; Reza Eftekhari Gol; Saied Bokaie; Behnaz Beygi (Society of Diabetic Nephropathy Prevention, 2019)
Introduction: The definition of the distance between the mean and reference value for the glomerular filtration rate (GFR) has been the topic of few performed studies, which resulting in an inconsistent mean difference. Objectives: This study was aimed to determine the normal GFR reference range for Iranian population and its comparison with global average. Patients and Methods: Data of the study population was extracted from Sina Health Record System (SinaEHR®). Based on the blood creatinine level, the GFR was calculated by Cockcroft- Gault formula. Using statistical analyses and independent t-test, GFR distribution was evaluated by the STATA software. Results: In this study the mean GFR in the Iranian population was estimated as 111.52 mL/ min/1.73m2 (CI: 111.30-111.73). When comparing results of this study with an international meta-analysis, it was revealed that before 45 years, the mean GFR in the Iranian population is higher than the standard mean value in the meta-analysis, whereas it is lower than the mentioned value after the age of 45 years. Moreover, the results demonstrated a significant difference in the mean GFR between men and women over 40 years of age (P<0.001). In those cases suffering from hypertension, hyperlipidemia or diabetes, the mean GFR was lower than healthy individuals (P<0.05), however, this difference was not significant for diabetic patients (P=0.580). Conclusion: The difference between our large population-based study and meta-analysis shows the need for more precise studies to better determine standard range of GFR in the Iranian population.